ENVELHECIMENTO, FAMÍLIA E POLÍTICAS SOCIAIS - Leonia Capaverde Bulla (Universidade Federal do Maranhão, 2010)
The Brazilian reality presents an increasing growth of the aged population as well as the increase of chronic- degenerative illnesses, what causes specific impacts on the elder ́s quality of life as well as on their families ́ quality of life. What has to be considered is that the social support offered to families in order to take care of the eldery is actually too scarce. Many rights of the elderies, foreseen by the Brazilian legislation, have not yet been put into practice, therefore have not been guaranteed by Social Policies.